AVTONOM ROBOTLAR HARAKAT TRAEKTORIYASINI OPTIMALLAShTIRISh USULLARINI IShLAB ChIQISh - Djaykov, G.M.; Perdebaev, U.B. (SCIENCE and SOCIETY, 2025)
This paper presents the design of an autonomous robot controlled via GPS navigation and the development of its motion algorithm. The robot follows predefined waypoints and estimates its position by fusing GPS and compass data. The paper provides the navigation algorithm block diagram, sensor data filtering techniques, and simulation results obtained in the Python environment. The results demonstrate that the robot can reliably and accurately reach target waypoints and operate effectively even under GPS error conditions (±2 m).
Keywords: autonomous robot; GPS navigation; compass; sensor data filtering; motion algorithm; simulation